Calculation of the Intermetallic Layer Thickness in Cold Metal Transfer Welding of Aluminum to Steel - Silvayeh, Zahra (Materials (Basel), 2018)
The intermetallic layer, which forms at the bonding interface in dissimilar welding of aluminum alloys to steel, is the most important characteristic feature influencing the mechanical properties of the joint. In this work, horizontal butt-welding of thin sheets of aluminum alloy EN AW-6014 T4 and galvanized mild steel DC04 was investigated. In order to predict the thickness of the intermetallic layer based on the main welding process parameters, a numerical model was created using the software package Visual-Environment. This model was validated with cold metal transfer (CMT) welding experiments. Based on the calculated temperature field inside the joint, the evolution of the intermetallic layer was numerically estimated using the software Matlab. The results of these calculations were confirmed by metallographic investigations using an optical microscope, which revealed spatial thickness variations of the intermetallic layer along the bonding interface.